Beginning OS X Lion Apps Development - Warner, Robert; Privat, Michael (Apress : Imprint: Apress, 2011)
With the Mac App Store launch in early 2011, a new age in Mac development began. Look for many of the cool apps for iPhone and iPad coming to an iMac or MacBook Pro near you! Beginning OS X Lion Apps Development explains how to develop OS X Lion-based apps and publish them in the Mac App Store. It begins with the basics of Objective-C and Cocoa, and then moves through all the topics necessary to build and publish your first successful Mac apps!   Get started with Objective-C and Xcode Build your first complete apps that integrate well with Mac OS X Publish your apps on the Mac App Store If you're new to Mac or new to iPhone or iPad apps development, and looking to develop apps for the Macbook Pro or Mac desktop, this book is for you!